Physical and mechanical study of sustainable repair mortar incorporated with maguey juice - Hinostroza Maravi, Heydi Karina (2025)
The objective of the project is to evaluate the physical and mechanical properties of the repair mortar incorporated with maguey juice for the repair of structural pathologies in the city of Huancayo. The construction sector has been growing over the years, but natural phenomena such as earthquakes and seismic events also occur daily, causing destruction and structural damage, and their repairs are becoming more and more costly. For this reason, the use of maguey juice as a natural additive in mortar was proposed to find out if it improves or worsens the properties of the mortar. To fulfill the objective of the research, an experimental study was carried out to find the physical and mechanical properties of the mortar. Tests of fluidity, air content, setting time, compressive strength, flexural strength, and mortar shrinkage test were carried out at 7, 14 and 28 days of curing with dosages of 0%, 3%, 5% and 7% of maguey juice based on a standard mix design of 260 kg/cm² with the ACI method. It was recommended to apply the 5% percentage of maguey juice, since that dosage was the one that provided the highest compressive strength reaching a value of 280.56 kg/cm², also a higher flexural strength was achieved having a value of 77.49 kg/cm². Additionally, with the dosage of 5% maguey juice, optimal values were obtained in relation to the physical properties of the mortar in its fresh state. Finally, it was concluded that by using dosages higher than 5% maguey juice , the physical and mechanical properties of the mortar tend to worsen.